2012
DOI: 10.1007/s13197-012-0667-2
|View full text |Cite
|
Sign up to set email alerts
|

Minerals and antinutrients profile of rabadi after different traditional preparation methods

Abstract: Rabadi is a cereal and buttermilk based traditional fermented recipe of western region of India. There are many traditional preparation methods, which may alter biochemical composition of rabadi, therefore, in the present study, role of traditional processings (cooking, fermentation, dehulling, utensil, preparation methods and cereals) on minerals and antinutrients of pearl millet, wheat flour and refined wheat flour rabadi was investigated on fresh weight basis. Results showed that the process of cooking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Domestic processing techniques have been found to reduce significantly the levels of phytates and tannins by exogenous and endogenous enzymes formed during processing. Reductions of such antinutritional factors by processing methods such as gamma irradiation, dehulling, soaking, sprouting, cooking, malting and fermentation have been documented by many researchers (Abdelhaleem et al 2008;Bains et al 2011;Ertas and Turker 2012;Gupta and Nagar 2012;Idris et al 2005;Obizoba and Atii 1994;Osman et al 2012) and still progressing. It has been reported that germination of various pearl millet cultivars increased significantly the HCl-extractable parts of both major and trace minerals, and also reduced significantly (P≤0.01) the phytic acid and polyphenols contents of millet cultivars (AbdelRahaman et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Domestic processing techniques have been found to reduce significantly the levels of phytates and tannins by exogenous and endogenous enzymes formed during processing. Reductions of such antinutritional factors by processing methods such as gamma irradiation, dehulling, soaking, sprouting, cooking, malting and fermentation have been documented by many researchers (Abdelhaleem et al 2008;Bains et al 2011;Ertas and Turker 2012;Gupta and Nagar 2012;Idris et al 2005;Obizoba and Atii 1994;Osman et al 2012) and still progressing. It has been reported that germination of various pearl millet cultivars increased significantly the HCl-extractable parts of both major and trace minerals, and also reduced significantly (P≤0.01) the phytic acid and polyphenols contents of millet cultivars (AbdelRahaman et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nigerian traditional dish made from cereal called ogi is rich in lysine, tryptophan, and vitamin B2 contents, whereas vitamin A and flavonoid contents were reduced [115]. Indian traditional fermented dish called rabadi made from pearl millet was studied for the effect of fermentation on biochemical composition that revealed the increased amount of protein and reduced fat, and crude fiber and also increased the flavonoid content [126]. Fermentation significantly reduces the antinutrients (trypsin, amylase inhibitor, and phytic acid) except tannin.…”
Section: Soaking Fermentation Enzymatic Hydrolysis Andmentioning
confidence: 99%
“…The separation of medicinally active portions of plant (and animal) tissues using selective solvents and standard procedures is referred to as extraction in the pharmaceutical industry (Gámiz-Gracia and Luque de Castro, 2000). Maceration (Gupta and Nagar, 2012), Tambun et al (2021) infusion (Stanciauskaite, et al , 2021), percolation, digestion, decoction, hot continuous extraction (Soxhlet), aqueous-alcoholic extraction by fermentation, counter-current extraction, microwave-assisted extraction, ultrasound extraction (sonication), supercritical fluid extraction and phytonic extraction are some of the common techniques used to extract medicinal plants (with hydrofluorocarbon solvents). Hydro-distillation techniques (water distillation, steam distillation, water and steam distillation), hydrolytic maceration followed by distillation, expression and enfleurage (cold fat extraction) can all be used to extract aromatic plants.…”
Section: Natural Products As Green Corrosionmentioning
confidence: 99%
“…The separation of medicinally active portions of plant (and animal) tissues using selective solvents and standard procedures is referred to as extraction in the pharmaceutical industry (G amiz-Gracia and Luque de Castro, 2000). Maceration (Gupta and Nagar, 2012), Tambun et al (2021) infusion (Stanciauskaite, et al, 2021) (Barbero, 2021).…”
Section: Extraction Processmentioning
confidence: 99%